Interpretasi ayat Al-Qur’an dan hadis: Pelestarian alam dan lingkungan - Ilmiyah, Nahdliyatul; Zakiyya, Amelda (Maliki Interdisciplinary Journal, 2026)
This paper explores the importance of environmental and nature conservation from the perspective of the Qur'an and Hadith. As the primary guide for Muslims, the Qur'an teaches that humans have a responsibility to maintain balance and sustainability on Earth. In Islam, the relationship between humans and nature is interconnected, where caring for and preserving the environment is considered an act of worship to Allah SWT. Environmental degradation, whether caused by natural factors or human actions, is a critical issue that requires serious attention. Research findings reveal that there are ten verses in the Qur'an explicitly commanding environmental conservation, such as QS. Al-A'raf: 56, which prohibits acts of destruction on Earth. Furthermore, the Hadith of the Prophet emphasizes the importance of actions such as planting trees, even in dire situations like the approach of the Day of Judgment. This paper, using a qualitative descriptive approach, examines Qur'anic verses and Hadiths related to environmental preservation, as well as the negative impacts of neglecting this responsibility. The emphasis on concrete actions, such as reforestation and natural resource management, reflects the commitment of Muslims to fulfilling their role as responsible stewards of the Earth.